2016
DOI: 10.1016/j.jamcollsurg.2016.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Partial Resuscitative Endovascular Balloon Occlusion of the Aorta in Swine Model of Hemorrhagic Shock

Abstract: In a porcine hemorrhagic shock model, P-REBOA resulted in more physiologically tolerable hemodynamic and ischemic changes compared with C-REBOA. Additional work is needed to determine whether the benefits associated with P-REBOA can both extend the duration of intervention and increase survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 39 publications
2
110
1
4
Order By: Relevance
“…In a porcine hemorrhagic shock model, Russo et al . showed that partial balloon occlusion of the aorta (pREBOA) resulted in more physiologically tolerable hemodynamic and ischemic changes compared with complete occlusion [24]. Therefore, we believe it is important with a standardized procedure in REBOA to include either a balloon deflation regime or pREBOA.…”
Section: Discussionmentioning
confidence: 99%
“…In a porcine hemorrhagic shock model, Russo et al . showed that partial balloon occlusion of the aorta (pREBOA) resulted in more physiologically tolerable hemodynamic and ischemic changes compared with complete occlusion [24]. Therefore, we believe it is important with a standardized procedure in REBOA to include either a balloon deflation regime or pREBOA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous large animal studies have confirmed its efficacy at preventing early death from exsanguination, with 100% survival during the “pre-hospital” intervention phase. 16, 17 However, the duration of REBOA is finite due to the adverse consequences of prolonged complete aortic occlusion on both proximal and distal vascular beds. 1, 11 This poses a significant challenge in scenarios where prolonged intervention is required, such as extended transport distances, prolonged care in austere environments, or mass casualty situations.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, REBOA is only a temporary solution and a definitive bleeding control must follow. One of the major problems of REBOA is the ischemia-reperfusion organ injury followed by multiple organ failure that might be prevented by short REBOA time, intermittent REBOA (iREBOA), Zone III REBOA and new methods as partial REBOA (pREBOA) described lately [67, 75, 76]. …”
Section: Methodsmentioning
confidence: 99%